FORMATION OF THE LEGAL SYSTEM IN BUKHARA EMIRATE (IN THE PERIOD OF DONYOLBIY) (World Bulletin of Social Sciences, 2024)
In this article, the formation and development of the legal system in the Bukhara Emirate during the time of Amir Donyolbi, as well as the implementation of various issues in the management of the society, were carried out in consultation
Keywords: Legal system; Society; Khoja; court